2019
DOI: 10.1002/jcsm.12374
|View full text |Cite
|
Sign up to set email alerts
|

LncIRS1 controls muscle atrophy via sponging miR‐15 family to activate IGF1‐PI3K/AKT pathway

Abstract: Background Recent studies indicate important roles for long noncoding RNAs (lncRNAs) in the regulation of gene expression by acting as competing endogenous RNAs (ceRNAs). However, the specific role of lncRNAs in skeletal muscle atrophy is still unclear. Our study aimed to identify the function of lncRNAs that control skeletal muscle myogenesis and atrophy. Methods RNA sequencing was performed to identify the skeletal muscle transcriptome (lncRNA and messenger RNA) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
139
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 43 publications
0
139
0
Order By: Relevance
“…Conversely, LINC00673 was identified to play a role in tumorigenesis in a variety of malignancies [11][12][13][14][15]. A rapidly growing number of studies have suggested that cytoplasmic lncRNAs are essential mediators of intracellular signaling pathways and are involved in regulating mRNA stabilization and transport as well as microRNA sponging [16][17][18]. Although LINC00673 has been implicated in the regulation of breast cancer cell metastasis via the modulation of epithelial-mesenchymal transition (EMT) in breast cancer [19], it remains to be seen whether LINC00673 acts as a competing endogenous RNA (ceRNA) to promote cell proliferation in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, LINC00673 was identified to play a role in tumorigenesis in a variety of malignancies [11][12][13][14][15]. A rapidly growing number of studies have suggested that cytoplasmic lncRNAs are essential mediators of intracellular signaling pathways and are involved in regulating mRNA stabilization and transport as well as microRNA sponging [16][17][18]. Although LINC00673 has been implicated in the regulation of breast cancer cell metastasis via the modulation of epithelial-mesenchymal transition (EMT) in breast cancer [19], it remains to be seen whether LINC00673 acts as a competing endogenous RNA (ceRNA) to promote cell proliferation in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the diverse mechanisms for modulating insulin sensitivity in skeletal muscle cells enable exploring how this candidate lncRNA regulated these genes from the co-expression network. Consistent with their predominantly in cytoplasmic localization, muscle-derived lncRNAs have been increasingly described as miRNA sponges with targeting downstream genes [69,70]. For example, muscle-enriched lncRNA H19 acted to enhance muscle insulin sensitivity like a sponge by sequestering let-7 targeting dual specificity phosphatase 27 (DUSP27) expression levels [68].…”
Section: Discussionmentioning
confidence: 99%
“…For example, linc-RAM promotes the assembly of the MyoD-Baf60c-Brg1 complex on the regulatory elements of myogenic genes by directly binding MyoD [9]. In addition, lncIRS1 regulates IRS1 expression and promotes skeletal muscle myogenesis through acting as a sponge for the miR-15 family [10]. LncRNAs usually perform different functions depending on their subcellular localization.…”
Section: Introductionmentioning
confidence: 99%